1987
DOI: 10.1128/aac.31.10.1613
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin antagonizes inhibitory effects of pyrimidine 2',3'-dideoxynucleosides but enhances inhibitory effects of purine 2',3'-dideoxynucleosides on replication of human immunodeficiency virus in vitro

Abstract: The combined antiviral effects of various 2',3'-dideoxynucleosides and ribavirin on the replication of human immunodeficiency virus type 1 in MT-4 cells have been examined. Ribavirin antagonized the antiviral activity of the pyrimidine 2',3'-dideoxynucleosides (3'-azido-2',3'-dideoxythymidine, 2',3'-dideoxythymidin-2'-ene, 2',3'-dideoxycytidine, and 2',3'-dideoxycytidin-2'-ene), but enhanced the antiviral activity of the purine 2',3'-dideoxynucleosides (2',3'-dideoxyadenosine and 2',3'-dideoxyguanosine). Combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(70 citation statements)
references
References 29 publications
7
63
0
Order By: Relevance
“…Altered phosphorylation is the most probable explanation for the decreased anti-HIV activity of ZDV in the presence of ribavirin in MT-4 cells (Baba et al, 1987). However, as shown in Table 2, ribavirin does not affect ddC phosphorylation and therefore would not be expected to inhibit its antiviral activity.…”
Section: Discussionmentioning
confidence: 97%
“…Altered phosphorylation is the most probable explanation for the decreased anti-HIV activity of ZDV in the presence of ribavirin in MT-4 cells (Baba et al, 1987). However, as shown in Table 2, ribavirin does not affect ddC phosphorylation and therefore would not be expected to inhibit its antiviral activity.…”
Section: Discussionmentioning
confidence: 97%
“…RBV has been shown to be synergistic in combination with ddl, but antagonistic in combination with AZT (Baba et al, 1987;Vogt et al, 1987;Balzarini et al, 1990Balzarini et al, , 1991. This has been attributed to the inhibition of IMP dehydrogenase by RBV, causing on the one hand increased phosphorylation of ddl (through increased IMP levels) and on the other hand decreased phosphorylation of AZT (through increased dTIP pools and feedback inhibition of thymidine kinase).…”
Section: Discussionmentioning
confidence: 99%
“…RBV also enhances the anti-HIV activity of ddl when these two Hao et a/., 1988;Huang et sl., 1990;Balzarini et at. 1991b;Tornevik et a/., 1991;De Glercq, 1992). drugs are combined in vitro and in Vivo (Balzarini et al, 1990(Balzarini et al, , 1991a, whereas it is antagonistic with AZT (Baba et al, 1987;Vogt et al, 1987). These effects are thought to be a result of the effect of RBV on IMP and dTIP pools.…”
Section: Introductionmentioning
confidence: 99%
“…Combination of different anti-HlV drugs may result in diminished toxicity, reduced risk of resistance development and/or synergistic antiviral activity, depending on decreased dosing of the individual drugs, complementarity of mutations in the viral genome and/or action at different target sites in the virus replication cycle. In fact, examples of antiviral synergy (such as ribavirin and ddI) (Baba et al, 1987b), additivity (AZT and acyclovir or gan- ciclovir) (Smith & Pagano, 1991;Medina et al, 1992) and antagonism (ribavirin and pyrimidine dideoxynucleoside analogues such as AZT) (Vogt et al, 1987) have been reported, and in a number of cases the molecular basis for the underlying mechanism of action has been elucidated.…”
Section: 5mentioning
confidence: 99%